English Verb “Catch” and Its Related Verbs in Buginese Language: A Comparative Study - Rahmaniar Rahmaniar; Hamzah A. Machmoed; Sukmawaty Sukmawaty (ELS Journal on Interdisciplinary Studies in Humanities, 2022)
Catch verb refers to something being brought into such position. All verbs are transitive verb and specification of locus is obligator and other it is optional. The aims of this research were (1)To identify related Verbs of English “Catch” Verb in Buginese Language. (2) To explain the similarities and differences of English Verb, “Catch” and Its Related Verbs in Buginese Language in terms of semantical and grammatical construction. English data were collected from Corpus of Contemporary American English (COCA), while data of Buginese were obtained from field research through process of observation and in depth interview. Both of the data were analyzed with description and qualitative analysis. The result of this research shows that (1) there is one kind of “Catch” verb that use in English. While, in Buginese language there are eight kinds of “Catch” verbs that different in semantic aspect. They are mattikkeng, mattimang, majjaleppa’, mattado’, marrippung, majjala, mattada, and massero’ (2) The main differences of Verb “Catch” in English and Buginese Language can be seen from clause structure and movement to brought something into such position. From clause structure, In English a NP is followed by VP, while in Buginese is permissible that VP is followed by NP that marked by suffix –I in VP. From movement aspect, divided into three; normal movement, medium movement, and hard movement.